ANÁLISE NUMÉRICA 3D DA ESTABILIDADE DE TALUDES DE GRANDE ALTURA EM MINAS A CÉU ABERTO - Gómez, Jorge; Garcia, Deysi M.; Romanel, Celso (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Currently one of the major mining companies in Peru is interested in establishing alternative workflows to remove the maximum mineral amount in a minimum time schedule, making as high as possible the performance of the investment. To achieve these goals, but maintaining the safety of operations, engineering analysis must be carried out to estimate the inclination of the open pit slopes and the total depth of excavation. The main factor of importance is to obtain the steepest angle of inclination to reduce the removal of the sterile material, thereby lowering the mining extraction costs. Of course, a gradual slope increasing may create risks of slope instability, compromising the safety of mining operations, with potential risk for loss of life as well as economic, environmental and social disasters with interruption or eventual closure of the mining facilities. The final excavation design is subject to factors such as the geomechanical properties of the rock mass and characteristics of the regional geological structures. In this work the slope stability of the open pit mine of Pampa de Pongo is investigated through numerical analysis using 2D and 3D finite element models. From the computed results it was observed that the out of plane displacement component introduced a significant effect on the rock mass behaviour.